PENGARUH STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN KINERJA PERUSAHAAN SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2024) - Fitri Giat Lestari,; Diana Sari, (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to analyze the effect of capital structure, firm size, and firm growth on firm value with financial performance as an intervening variable in the banking sector listed on the Indonesia Stock Exchange during 2020–2024. The sample was determined using purposive sampling, and the data were analyzed with Structural Equation Modeling (SEM) using AMOS. The results show that capital structure and firm size have a positive effect on financial performance, while firm growth reduces performance. On the other hand, capital structure does not affect firm value, whereas firm growth and firm size increase firm value. Financial performance itself has a negative effect on firm value. Furthermore, financial performance does not mediate the relationship between capital structure, firm growth, and firm size with firm value, indicating that its intermediation role in the banking sector remains relatively weak.